2005
DOI: 10.1111/j.1365-2036.2005.02553.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily treatment with esomeprazole is superior to that taken on‐demand for maintenance of healed erosive oesophagitis

Abstract: SUMMARYBackground: On-demand therapy with esomeprazole is effective for long-term treatment of non-erosive gastrooesophageal reflux disease, but it has not been evaluated in erosive gastro-oesophageal reflux disease. Aims: To compare endoscopic and symptomatic remission over a 6-month period when patients with healed erosive gastro-oesophageal reflux disease are treated with esomeprazole 20 mg, either once daily or on-demand. Methods: Patients with verified erosive reflux oesophagitis of Los Angeles grades A-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 22 publications
2
49
0
10
Order By: Relevance
“…Our findings also demonstrated that there was no significant difference in overall satisfaction and symptoms score between the on-demand therapy with 20 mg vonoprazan and maintenance therapy with PPI, suggesting that the efficacy of the treatment would be equivalent for the 3 groups. Regarding the remission rate of on-demand therapy with PPI for RE, a study demonstrated that remission is maintained in 78% of grade A and 65% of grade B patients who underwent a 6-month on-demand therapy with 20 mg esomeprazole [23]. We found that a higher proportion of patients remained in remission when receiving on-demand therapy with 20 mg vonoprazan, with 100% of grade A and 78.9% of grade B patients.…”
Section: Discussionmentioning
confidence: 70%
“…Our findings also demonstrated that there was no significant difference in overall satisfaction and symptoms score between the on-demand therapy with 20 mg vonoprazan and maintenance therapy with PPI, suggesting that the efficacy of the treatment would be equivalent for the 3 groups. Regarding the remission rate of on-demand therapy with PPI for RE, a study demonstrated that remission is maintained in 78% of grade A and 65% of grade B patients who underwent a 6-month on-demand therapy with 20 mg esomeprazole [23]. We found that a higher proportion of patients remained in remission when receiving on-demand therapy with 20 mg vonoprazan, with 100% of grade A and 78.9% of grade B patients.…”
Section: Discussionmentioning
confidence: 70%
“…Two recent reviews summarizing on-demand studies showed that on-demand PPI therapy was effective for uninvestigated and nonerosive reflux disease, and possibly mild esophagitis as well [13,29]. On the other hand, it was shown that on-demand therapy for healed esophagitis patients increased endoscopic remission compared to continuous treatment, which was more pronounced for the more severe baseline grades [30]. Unfortunately, the level of symptom control and the amount of medication used by patients with endoscopic remission were not described in this publication.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to on-demand treatment, the general practitioner should inform the patient about risks and alarm symptoms. Attention should be paid to recurrence of heartburn, as this specific symptom appeared to be strongly correlated with onset of esophagitis in on-demand treated patients with a history of esophagitis [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Some data indicate that continuous use of PPI in the maintenance treatment of GERD is superior to on-demand use of PPI for the prevention of both endoscopic recurrence and symptomatic recurrence (19,20). Sjöstedt et al (19) randomized 477 patients, who had erosive esophagitis and who experienced remission with a therapy of esomeprazole 40 mg/day, as groups receiving continuous or on-demand esomeprazole at the maintenance dose.…”
Section: Recommendationsmentioning
confidence: 99%
“…Sjöstedt et al (19) randomized 477 patients, who had erosive esophagitis and who experienced remission with a therapy of esomeprazole 40 mg/day, as groups receiving continuous or on-demand esomeprazole at the maintenance dose. While the remission rate was found to be 81% in the continuous therapy group, this rate was 58% in the on-demand group at the end of the 6 th month (p<0.0001).…”
Section: Recommendationsmentioning
confidence: 99%